Gestión y política de los bosques en el Perú - Suárez de Freitas Calmet, Gustavo (2023)
A review of the situation of forest management in Peru is carried out, particularly in the Amazon region, using the United Nations' definition of sustainable forest management as a reference. This definition is based on: (i) the extent of forest resources; (ii) forest biological diversity; (iii) the health and vitality of forests; (iv) productive functions; (v) protective functions; (vi) socio-economic functions; and (vii) the regulatory, institutional, and policy framework. Based on the review of available information on these aspects, the current situation of deforestation is illustrated, which reduces forest coverage and diminishes the provision of ecosystem services. Risks of unsustainability in the utilization of certain resources, such as species listed in the CITES Convention, are identified. Inappropriate situations regarding limited access to resources for certain stakeholders are highlighted, as well as delays in the implementation of certain instruments that would help solve key issues for rural producers, such as land-use agreements (leasing) for agroforestry systems. A review of the legal framework and governance structure developed is conducted, which presents distinctive positive features such as the equal representation of indigenous peoples, the state, and the non-public sector in the Board of Directors, and the existence of significant participation spaces like the Forest and Wildlife Management Committees (CGFFS), which have not been established. The discussion briefly addresses whether the identified current limitations are a result of a legal and organizational design issue or rather a management problem, in order to guide necessary interventions for improving management outcomes.